2023
DOI: 10.1002/eap.2848
|View full text |Cite
|
Sign up to set email alerts
|

Urban soil quality deteriorates even with low heavy metal levels: An arthropod‐based multi‐indices approach

Abstract: Urban-induced habitat conversion drastically changes soil life in a variety of ways.Soil sealing, human disturbance, habitat fragmentation, industrial and vehicular pollution are the main causes of urban soil degradation. Soil arthropods, as one of the most abundant and diverse group of soil fauna, are involved in many soil processes that are of great importance in maintaining soil health and multifunctionality. Nevertheless, soil quality is still mainly characterized by physical, chemical, and microbiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 81 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Sim i lar i ties were ob served in Pol ish soil, though in terms of ur ban soil, the mean con tent of Cd, Zn, Cu were higher than the back ground val ues of the Pol ish soils (Skorbi³owicz et al, 2021). In Hun gary, on av er age, the HM con cen tra tions were be low the pol lu tion limit val ues in ur ban green spaces (Tóth et al, 2023), whereas in green ter ri to ries of Lith u a nia Cu and Zn were found above the BC limit val ues. Living ter ri to ries such as cit ies all across the world dif fer from one an other in terms of pop u la tion den sity and rate of ur ban iza tion.…”
Section: Discussionmentioning
confidence: 85%
“…Sim i lar i ties were ob served in Pol ish soil, though in terms of ur ban soil, the mean con tent of Cd, Zn, Cu were higher than the back ground val ues of the Pol ish soils (Skorbi³owicz et al, 2021). In Hun gary, on av er age, the HM con cen tra tions were be low the pol lu tion limit val ues in ur ban green spaces (Tóth et al, 2023), whereas in green ter ri to ries of Lith u a nia Cu and Zn were found above the BC limit val ues. Living ter ri to ries such as cit ies all across the world dif fer from one an other in terms of pop u la tion den sity and rate of ur ban iza tion.…”
Section: Discussionmentioning
confidence: 85%
“…45% of the 174 studies on European urban soils did not provide data on standard deviation (Binner et al, 2023)). Furthermore, only a limited number of studies have explored the connection between MTE pollution and soil fauna communities, and the results obtained from these investigations vary considerably (Fiera, 2009;Pižl and Josens, 1995;Santorufo et al, 2012;Tóth et al, 2023;Yu et al, 2022). The scarcity of research in this area stands in stark contrast to the abundant literature available on MTE toxicity in soil organisms, particularly earthworms (Sivakumar, 2015;Yadav et al, 2023).…”
Section: Introductionmentioning
confidence: 99%